Effectiveness of crude oil degrading fungi isolated from petroleum hydrocarbon contaminated soil in Siak, Riau - Endang Maya Sari; Riryn Novianty; Amir Awaluddin; Saryono; Nova Wahyu Pratiwi (Indonesian Society for Biochemistry and Molecular Biology, 2019)
Background: Biodegradation of petroleum hydrocarbon needs a specific technique called bioremediation to remove the environmental pollutants. Several indigenous microorganisms including fungi, bacteria, and actinomycetes are effective agents in degrading petroleum derivatives, aliphatic and polyaromatic hydrocarbons (PAHs). Objective: This research aimed to investigate indigenous fungi isolates from petroleum hydrocarbon contaminated soil in Siak which are capable to degrade hydrocarbon. Methods: The competence of indigenous fungi was isolated from a crude oil-contaminated soil which collected from one of oil-field in Siak, Riau. The effectiveness of isolates on the degradation crude oil was tested by culturing the isolates in Bushnell-Haas broth containing crude oil (5% v/v) for 16 days. A decrease in pH, change in optical density and amount of CO2 released were recorded to indirectly indicate the crude oil degradation by the fungi. To measure the percentage of crude oil biodegradation, gravimetric analysis was utilized. Results: The two colonies were selected and identified as Aspergillus sp LBKURCC151 and Penicillium sp LBKURCC153. The results showed that Aspergillus sp LBKURCC151 reached a higher level (61%) of biodegradation after 16 days under the optimum conditions in degrading total petroleum hydrocarbon than Penicillium sp LBKURCC153 (46%). Conclusion: These results indicated that Aspergillus sp LBKURCC151 and Penicillium sp LBKURCC153 are potential degraders for bioremediation in crude oil-contaminated area.